Covalent organic framework with active C=O/C=N groups for high performance cathode material for lithium‐ion batteries. (9th June 2022) - Liu, Yang; Cai, Xuesong; Chen, Dinggui; Qin, Yan; Chen, Yuan; Chen, Jinxiang; Liang, Chenglu
Summary: The large‐scale applications of energy storage system via lithium‐ion batteries (LIBs) put forward demands for high capacity, high safety, and low cost of materials. Covalent organic polymers have attracted extensive attention because of their high capacity, flexible structural design, high safety, abundance, and low cost. Here, 2, 3, 5, 6‐tetraamino‐p‐benzoquinone and hexaketocyclohexane octahydrate were chosen as monomers to construct the covalent organic framework (TH‐COF) cathode materials with active C=O and C=N groups. The TH‐COF was further composed with reduced graphene oxide (rGO) and the prepared TH‐COF/rGO cathode provided a capacity of 135 mAh g −1 after 600 cycles at 1 C current density. In addition, after 100 cycles, the cathode delivered capacities of 118 and 73 mAh g −1 at the high current densities of 5 C and 20 C, respectively, displaying superior rate performances. The TH‐COF/rGO electrode exhibited high capacity and stability, making it a promising cathode material for the next generation LIBs. Abstract : The covalent organic framework (TH‐COF)/reduced graphene oxide cathode materials with active C=O and C=N groups displayed superior rate performances. At the current density of 20C, the cathode can deliver a high capacity of about 95 mAh g −1 .